1962
DOI: 10.1111/j.1365-2621.1962.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of Myoglobin and Hemoglobin in Tuna Flesh

Abstract: Amounts of myoglobin and hemoglobinwere determined in light and dark muscle of yellowfin tuna, Neothunnus macropterus. Myoglobin concentration ranged from 0.37 to 1.28 mg/g wet weight in light muscle and from 5.3 to 24.4 mg/g in dark muscle; hemoglobin concentrations ranged from 0.12 to 0.58 mg/g in light muscle and from 0.5 to 3.8 mg/g in dark muscle. The fish were divided into two groups on the basis of means of capture, i.e., taken on hooks from a bait boat,-or seined. Average percentage of hemoglobin was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…Dark muscle, both superficial and deepseated, contained more hemoglobin, myoglobin and cytochrome c than the ordinary muscles (Sikorski et al, 1990). Muscle of yellowfin tuna contained myoglobin ranging from 37 to 128 mg% in light muscle and 530-2440 mg% in dark muscle (Brown, 1961). Sardine dark muscle comprised myoglobin 2.9 times greater than mackerel dark muscle.…”
Section: Chemical Compositions and Myoglobin In Sardine And Mackerel mentioning
confidence: 99%
“…Dark muscle, both superficial and deepseated, contained more hemoglobin, myoglobin and cytochrome c than the ordinary muscles (Sikorski et al, 1990). Muscle of yellowfin tuna contained myoglobin ranging from 37 to 128 mg% in light muscle and 530-2440 mg% in dark muscle (Brown, 1961). Sardine dark muscle comprised myoglobin 2.9 times greater than mackerel dark muscle.…”
Section: Chemical Compositions and Myoglobin In Sardine And Mackerel mentioning
confidence: 99%
“…Previous studies reported that the structural stabilities of scombridae fish Mbs clearly differ among species, although the sequence identities of amino acids were in the range of 91 − 99% (Ueki et al, 2004;2005;2006). Among them, skipjack tuna Mb was the most thermostable, and bullet tuna (Auxis rochei) Mb showed the lowest stability.…”
Section: Resultsmentioning
confidence: 99%
“…Mb concentration is also an excellent parameter of meat quality grade. Mb concentration should be very similar in a given species (Brown, 2006); therefore, it is likely that Mb was partially denatured and insolubilized. The extractability of Mb was reduced in lower grades of meat.…”
Section: Resultsmentioning
confidence: 99%
“…Tilapias are partly distributed as skinned fillets packed in transparent plastic bags, and so the color of the dark muscle is crucial to the commercial value of the product. The redness of this muscle is mainly due to the presence of a pigment protein, myoglobin (Mb) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%